The relationship between job satisfaction and health-related quality of life (HRQOL) amongst administrative workers in selected government bodies, Shah Alam / Khalid Amin Mat - Mat, Khalid Amin (2010)
This research is concerning the relationship between job satisfaction and Health-Related Quality of Life (HRQOL) amongst administrative workers in selected government bodies, Shah Alam. The Variance theory of job satisfaction comprising the dimensions of meaning, professionalization, financial, competence, orientation, work-related stress and supervision dimension was used as the supporting theory for this research. The aim of this study is to investigate the relationship between job satisfaction and HRQOL domains physiological health, psychological health and social health. The population of the study was 935 administrative workers working in eight different government bodies in Shah Alam. The sample size of the study consisting of 274 administrative workers from eight government bodies was randomly selected from the sampling frame. In order to investigate the level of job satisfaction and its relationship to HRQOL, a questionnaire containing two sections was developed. The first section on job satisfaction has 29 items while the second section considering the HRQOL domains has 16 items. As the result of the data analysis, the researcher found that the administrative workers were satisfied with their job in their overall level of job satisfaction. The most satisfied dimension of job satisfaction factor is the meaning dimension. The researcher also found that there is a positive relationship between job satisfaction with all domains of HRQOL including physiological health, psychological health and social health.